2023
DOI: 10.3390/biomedicines11020424
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Ameliorates the Hepatic Oxidative Damage and Fibrotic Effect Caused by Thioacetamide in Rats

Abstract: Vitamin D3 (VD3) is a sunshine hormone that regulates cellular proliferation, differentiation, apoptosis, and angiogenesis related to liver parenchyma. We used a thioacetamide (TAA)-induced hepatic fibrosis rat model in our study to investigate the beneficial roles of VD3 to overcome extensive liver fibrosis. Randomly, four equal groups (eight rats per group) underwent therapy for eight successive weeks: a control group, a group treated with TAA 100 mg/kg BW IP every other day, a group treated with VD3 1000 IU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Notably, TAS levels exhibited a significant increase. Similar findings to our results were reported in the previous studies regarding the impact of Vit D exposure on MDA and TOS levels [ 30 ]. As observed in this study, Vit D supplementation results in a reduction of ROS formation, an increase in the activity of antioxidant enzymes, and inhibition of lipid peroxidation [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Notably, TAS levels exhibited a significant increase. Similar findings to our results were reported in the previous studies regarding the impact of Vit D exposure on MDA and TOS levels [ 30 ]. As observed in this study, Vit D supplementation results in a reduction of ROS formation, an increase in the activity of antioxidant enzymes, and inhibition of lipid peroxidation [ 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, antioxidants are necessary to inhibit the generation of new free radicals to stop oxidative stress, and the administration of exogenous antioxidant chemicals can prevent ROSs from exerting their harmful effects [ 55 ]. For instance, several studies have reported the antioxidant effects of NAC [ 13 , 56 ], VitD3 [ 57 , 58 ], and Glut [ 59 , 60 ], highlighting their significant contributions to enhancing the mechanisms responsible for maintaining body homeostasis and safeguarding the health of body tissues. The data collected in this study demonstrate that the combination of NAC, VitD3, and Glut exerts a cooperative effect in all body districts analysed, indicating a possible new strategy to restore oxidative homeostasis of the body.…”
Section: Discussionmentioning
confidence: 99%
“…TAA is a classic liver toxin and also a potent carcinogen and mutagen, which can induce oxidative stress and sterile inflammation, leading to acute and chronic liver injury ( 28 , 29 ). TAA induces hepatotoxicity in mice and rats at doses ≥100 mg/kg.…”
Section: Chemical Induction Methodsmentioning
confidence: 99%
“…It is converted to metabolites TAA S-oxide and S, S-dioxide by cytochrome P450 enzymes and S, S-dioxide initiates toxicity by binding to lipids and proteins ( 24 ). TAA-induced liver injury is mainly caused by reaction metabolites secreted by TAA, which not only activate HSC, but also produce fibrinogen and growth factors, aiming to promote acute liver injury and chronic liver fibrosis ( 29 ).…”
Section: Chemical Induction Methodsmentioning
confidence: 99%